Representasi Relasi Kuasa Gender dalam Film Dua Hati Biru: Analisis Semiotika Peirce dalam Perspektif Patriarki Sylvia Walby - Devia Tantri Rachmani; Imaniar Dwi Retno Pangesti; Ike Desi Florina (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the representation of gender power relations in the film Dua Hati Biru using Charles Sanders Peirce’s semiotic analysis within the framework of Sylvia Walby’s theory of patriarchy. Employing a qualitative descriptive approach, the research analyzes selected scenes that depict wage labor, domestic labor, and workplace discrimination. The findings reveal that wage labor functions as the primary source of legitimacy and authority within family relations, regardless of gender, positioning economic control as the central axis of power. Domestic labor is portrayed as essential to family stability yet remains symbolically undervalued and naturalized as a moral obligation, particularly for women. Meanwhile, workplace discrimination is represented through implicit institutional norms that stigmatize women’s marital and maternal identities, compelling adaptation rather than structural change. Through icons, indexes, and symbols, the film constructs a subtle yet persistent patriarchal logic that normalizes gender inequality. This study concludes that Dua Hati Biru not only reflects social realities but also participates in reproducing patriarchal ideology by sustaining hierarchical distinctions between productive and reproductive labor within both domestic and professional spheres.